Maternal Reading Self-Efficacy Associated with Perceived Barriers to Reading. (12th January 2015) - Lin, Joyce; Reich, Stephanie M.; Kataoka, Sabrina; Farkas, George
Abstract : Although early reading practices impact a host of child literacy, language, and school outcomes, many parents do not read to their young children. One possible explanation for this lack of early literacy practices is mothers' feelings about their ability to successfully read to their children. A series of multiple regressions were used to explore whether new mothers' reading self-efficacy predicted their perceived barriers to reading to their 18-month-old children. Findings suggest that self-efficacy buffers against mother-centered (e.g., too tired), child-centered (e.g., toddler fussy), and structural (e.g., environmental distractions) barriers to reading. Given the importance of early literacy and that not all mothers read to their toddlers, increasing reading self-efficacy may offer a way to reduce perceived barriers to early literacy practices.